Dualism in Philosophical Studies - Anggrayni, Retno (Journal of Innovation in Teaching and Instructional Media, 2023)
In the educational context, the term dualism and dichotomy have the same meaning, namely the separation between general education and religious education. The terms also mean the separation between education system of Islamic and general educations. Moreover, talking about Islamic education is often addressed to Islamic institutions. Such perspectives are triggered by dichotomous view on education, differentiate in one side and equate on the other side. Consequently, the spirit value that is integrated into Islamic education is neglected. The terms, currently, have pervaded on the separation of general and Islamic subjects, public and madrasas Institutions, where the management has a policy respectively. The impacts are narrow minded in interpreting Islamic meaning, compartmentalization in science, and inequality of budgeting between Islamic and general education institutions. The offered alternative solutions are Islamization of knowledge, integration of science, and reposition of Islamic view, that means returning to the spirit value of Islamic education.